Formation and functions of arbuscular mycorrhizae in coastal wetland ecosystems: A review. Issue 1 (31st December 2022) - Wang, Xing-Qiang; Wang, Yan-Hong; Song, Yao-Bin; Dong, Ming
ABSTRACT: Context: Coastal wetlands are ecotones interspaced by land and ocean and are among the most sensitive and vulnerable ecosystems worldwide. They are unique in hydrological, edaphic, atmospheric, and biological characteristics, and play important roles in maintaining the ecological security and ecosystem services of coastal zones. Arbuscular mycorrhizae (AM) are symbiont composed of plant roots and arbuscular mycorrhizal fungi (AMF), which are soil-borne microorganisms widely distributed in various habitats. Many previous studies on mycorrhiza have focused on terrestrial ecosystems while few on wetlands, especially coastal wetlands. Method: We systematically reviewed previous relevant studies to explore the formation and functions of AM in coastal wetland ecosystems as well as the environmental factors that affect them. Habitat characteristics, morphological types, and species diversity of AMF in the coastal wetlands were summarized. Both responses of AMF to environmental factors during AM formation and the functions of AM in coastal wetlands were discussed. Result: AMF are worldwide distributed in coastal wetland and are mainly limited by flooding, hypoxia, soil pH, salinity and the host plants identification. AMF play important roles in coastal wetlands, involving promoting nutrient uptake of host plants, improving the characteristics of rhizospheric soil, and enhancing plant resistance to salt and flooding stress. Conclusion: More comprehensive studies of AMF in vitro in coastal wetlands would be helpful for the conservation and restoration of coastal wetland ecosystems in the changing world.